Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan, Pertumbuhan Aset dan Strukur Modal terhadap Kebijakan Dividen - Agnes Fanny Laurent; Agus Munandar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to examine how dividend policies impact manufacturing companies in the food and beverage subsector, including profitability, liquidity, company size, asset growth, and capital structure. Purposive sampling method was employed to select a sample of companies listed on the Indonesia Stock Exchange from 2018 to 2022. A total of 75 financial report data were obtained from 15 companies that met the sample criteria. Standard hypothesis tests, including autocorrelation, multicollinearity, normality, and heteroskedasticity, were part of the research process. With multiple regression analysis as the main approach, t-tests and coefficient of determination were applied to evaluate hypotheses regarding the influence of independent variables on the dependent variable. Profitability and company size show a positive correlation with dividend policies, while, on the other hand, dividend policies are not significantly influenced by liquidity, asset growth, and capital structure.